KARAKTERISTIK RESPON SISWA SEKOLAH DASAR DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH BERDASARKAN TAKSONOMI SOLO - Mohammad Sholeh (Jurnal Komposisi, 2021)
This research was purposed for knowing Students Respon  Characteristic in Problem Based Learning Model based on SOLO Taxonomy. We know that, taxonomy was able to help teacher and students on the learning process. It was used for facilitating mental process, and reach out the aims of learning process. This research is qualitative, which has three steps of analyses. The first step is data reduction, the second is data presentation, the last is data verification. This researchment proves that elementary school students’ cognitive are in multistruktural level. It is proved by ten of twelve students’ answer that stop on the third question, eventhough, two of them are in higher level. SOLO taxonomy is easy to do in learning process, it can help teachers to know students cognitive level, so that they are able to choice the best strategy that fit in to learning process.